Carbon nanotube and carbon dot mediated plasmid DNA delivery in cowpea leaves - Merve Saglam; Nikolaos Tsakirpaloglou; Aya Bridgeland; Robert Miller; Michael J. Thomson; Endang M. Septiningsih (PLoS ONE, 2026)
CRISPR-Cas9 technology has been widely used as a key molecular biology tool for crop improvement. However, the advance of this technology has been hindered by host species- or genotype-dependent tissue culture protocols and poor transformation efficiencies. Recent research has shown that plasmid DNA delivered by single-walled carbon nanotubes (SWCNTs) and carbon dots (CDs) can diffuse through plant cell walls, enabling the transient expression of genetic material in plant tissues. However, such an experiment has not been performed in legumes, most of which are considered recalcitrant species for transformation. In this study, we aim to investigate the capability of a SWCNT or CD-based plasmid delivery system in expressing a target gene in cowpea ( Vigna unguiculata ) leaves via infiltration using the β-glucuronidase ( GUS ) reporter gene. Further, we aim to see the potential of SWCNTs and CDs for a CRISPR-Cas9 gene construct delivery system, with phytoene desaturase ( PDS ) as the target gene. Our results showed that SWCNTs and CDs can deliver the GUS reporter gene construct in the surrounding area near the site of the infiltration, which results in the temporary expression of GUS by observing the blue color in this area. Likewise, infiltration of the CRISPR-Cas9 vectors targeting the PDS gene for the knockout resulted in multiplex editing and large deletions within the target gene. Overall, our findings pave the way for overcoming conventional DNA delivery challenges. However, further research is needed to explore optimal germline targets for plant tissues to avoid chimerism and to allow for more efficient CRISPR-Cas9 editing resulting in heritable mutations.